ANALISIS ATRIBUT BAURAN PEMASARAN YANG MEMPENGARUHI KEPUASAN KONSUMEN PISANG GORENG KIPAS KUANTAN-II DI KOTA PEKANBARU - Syafrini Rizki Rahmah; Fajar Restuhadi; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to knowing consumer interest level and attribute performance of marketing by using Importance-Performance Analysis (IPA) and to knowing consumer tendency base on consumer interest level and attribute performance of Pisang Goreng Kipas Kuantan-II. The data have been collected by share the question paper to the consumer in Pisang Goreng Kipas Kuantan-II market. Sample method in this research using convenience sampling, which do the sampling base on consumer permission to become participate. This research using a simple descriptive tabulation frequency analyse, Importance-Performance Analysis (IPA) and Multiatribute Fishbein method. The attribute which has interest level on average value that is package, taste, shop nametag, comfortable, mark, scent, nutrient contain, park area, and product availability with consumer interest value 5,65. The attribute which has performance attribute on average that is taste, mark, package, shop nametag, stoco limit, price, mature level around 5,53. The attribute which need to maintan base on Importance-Performance Analysis (IPA) is in Kuadran II that is taste , scent, package, mark, shop nametag, but the attribute which need to repair is in Kuadran I that is product availability, nutrient contain, park area, and comfortable. Consumer respon which analyse by using Fishbein attribute 562,29 which place on between scale good and very good. Kata kunci:   Consumer interest level, Performance, Diffusivity marketing, Pisang Goreng Kipas Kuantan-II